Pengaruh Social Media Marketing, Kualitas Pelayanan Dan Lokasi Terhadap Keputusan Pembelian Sate Taichan Goreng - Safira Sania; Mariah (STREAMING, 2022)
This study aims to determine how much influence the social media marketing, service quality, and location on purchasing decisions on Sate Taichan Goreng. This study uses a nonprobability sampling technique. The results of 132 respondents who processed using the SPSS Statistics 13 program showed that social media marketing variables influence purchasing decisions with a calculated T value> T table = 4.242> 1.978. Service quality variable influences the purchase decision with the calculated T value> T table = 2.710> 1.978. Location variable influences the purchase decision with a calculated T value> T table = 4.316> 1.978. Variables of social media marketing, service quality, and location simultaneously influence purchasing decisions with a calculated F value> F table = 4.695> 2.675. This explains that Ho is rejected and Ha is accepted, which means that social media marketing, service quality, and location variables affect purchasing decisions partially or simultaneously.